2015
DOI: 10.3389/fbuil.2015.00002
|View full text |Cite
|
Sign up to set email alerts
|

Application of Story-Wise Shear Building Identification Method to Actual Ambient Vibration

Abstract: Citation:Fujita K, Ikeda A and Takewaki I (2015) A sophisticated and smart story stiffness system identification (SI) method for a shear building model is applied to a full-scale building frame subjected to micro-tremors. The advantageous and novel feature is that not only the modal parameters, such as natural frequencies and damping ratios but also the physical model parameters, such as story stiffnesses and damping coefficients, can be identified using micro-tremors. While the building responses to earthq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Furthermore, when the building height is higher than the current model, the influence of the soil type and wind loadings on the stiffness identification should be investigated in more detail. It was reported that the SI method using the S model and the IDF for microtremor input on relatively soft soil can provide a reliable results (Fujita et al, 2015). On the other hand, the theoretical formulation to decrease the influence of the wind loading on the identification was studied by Koyama et al (2015) for rather low-rise buildings.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when the building height is higher than the current model, the influence of the soil type and wind loadings on the stiffness identification should be investigated in more detail. It was reported that the SI method using the S model and the IDF for microtremor input on relatively soft soil can provide a reliable results (Fujita et al, 2015). On the other hand, the theoretical formulation to decrease the influence of the wind loading on the identification was studied by Koyama et al (2015) for rather low-rise buildings.…”
Section: Discussionmentioning
confidence: 99%
“…used as the base input. These micro-tremors data were obtained at Disaster Prevention Research Institute of Kyoto University, Japan (Fujita et al, 2015). In following numerical examples, the bandlimited white noise is added to the output data as the measurement noise, i.e., horizontal and rotational accelerations, independently at each story.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…On the other hand, Nakamura (2000, 2005) developed a unique SI concept which is originally from the work by Udwadia et al (1978) for a shear building model (S model). Although the SI method by Nakamura (2000, 2005) was innovative, an additional effort should be provided in applying to actual data represented by micro-tremors (Ikeda et al, 2014;Fujita et al, 2015;Koyama et al, 2015). This may result from the small signal/noise (SN) ratio especially in the low frequency range.…”
Section: Introductionmentioning
confidence: 99%